The Recipe Club: A Tale of Food and Friendship - Israel Andrea (Polhemus Press, 2009)
Lilly and Val are lifelong friends, united as much by their differences as by their similarities. Lilly, dramatic and confident, lives in the shadow of her beautiful, wayward mother and craves the attention of her distant, disapproving father. Val, shy and idealistic—and surprisingly ambitious—struggles with her desire to break free from her demanding housebound mother and a father whose dreams never seem to come true.